2017
DOI: 10.3390/nu9070683
|View full text |Cite
|
Sign up to set email alerts
|

Meat and Seafood Consumption in Relation to Plasma Metabolic Profiles in a Chinese Population: A Combined Untargeted and Targeted Metabolomics Study

Abstract: We examined the relationship between different patterns of meat and seafood consumption and plasma metabolic profiles in an Asian population. We selected 270 ethnic Chinese men and women from the Singapore Prospective Study Program based on their dietary habits assessed with a validated food frequency questionnaire. Participants were divided into four subgroups: high meat and high seafood (n = 60), high meat and low seafood (n = 64), low meat and high seafood (n = 60), and low meat and low seafood (n = 86) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…Although a considerable number of attempts have been made to identify dietary biomarkers that reflect specific food and nutrient consumption by targeted approaches, conducting nontargeted research to explore unknown full-coverage metabolites is still a fairly new approach [12][13][14][15]. Additionally, global-scale epidemiological studies have reported comprehensive investigations, focusing on the relationships between food intake, metabolites, and disease risk [16][17][18][19]; however, only a few large-scale epidemiological studies among Asian populations have so far been reported [20][21][22], and further research on various regional characteristics of free-living individuals is expected.…”
Section: Introductionmentioning
confidence: 99%
“…Although a considerable number of attempts have been made to identify dietary biomarkers that reflect specific food and nutrient consumption by targeted approaches, conducting nontargeted research to explore unknown full-coverage metabolites is still a fairly new approach [12][13][14][15]. Additionally, global-scale epidemiological studies have reported comprehensive investigations, focusing on the relationships between food intake, metabolites, and disease risk [16][17][18][19]; however, only a few large-scale epidemiological studies among Asian populations have so far been reported [20][21][22], and further research on various regional characteristics of free-living individuals is expected.…”
Section: Introductionmentioning
confidence: 99%
“…One promising area of research to gain insight into these mechanisms involves applying metabolomics, the measurement and identification of circulating biomolecules, to observational and intervention studies of lifestyle exposures. Previous metabolomics studies have reported associations between lifestyle behaviors, particularly dietary intakes, and concentrations of the branched-chain amino acids (BCAAs) isoleucine, leucine and valine [11][12][13][14][15][16][17][18]. While these metabolites are innately involved in biological functions, BCAAs have also been consistently identified as risk factors for cardiometabolic diseases due to their strong association with insulin resistance [19], with accumulating evidence for causal effects [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another dietary intervention study has reported increased furan fatty acids after increased protein intake from fish and meat, including circulating levels of CMPF following consumption of a Mediterranean-type diet [235]. Plasma, serum, and urine CMPF has been observed also in free living populations across the Northern Hemisphere, where levels were associated with habitual dietary intake of fish and shellfish in several populations in Europe, China, and the USA [62, 236, 237]. Plasma as well as urine CMPF has also been observed to increase in hyperlipidemic patients after 600 mg/day of fish oil for 4 weeks and levels were still increased after 4 weeks’ wash-out [238].…”
Section: Resultsmentioning
confidence: 99%